Comparative Anatomical and Histological Study of the Liver in Three Species of Wild Birds in Iraq - Hussein A. Al-hamadawi (Journal of Global Pharma Technology, 2017)
The present study aims to know the morphological description and histological structure of the liver for three species of Iraqi wild birds (Laughing dove, White-throated Kingfisher and Common Kestrel) which represent different modes of feeding habits. To make this purpose a 24 sexually mature healthy birds were hunted from different areas of Al-shamyia city in Al-Qadisiyah province (8 birds from each species) , all birds were anesthetized and sacrificed after catch directly. The results of anatomical study showed that the liver for three species of birds were located in the middle of coelom cavity and it composed of two lobes, large right lobe and small left lobe in Laughing dove and White-throated Kingfisher ; But the left lobe is bigger than right lobe in Common Kestrel. On the other side the results showed a significant difference (P<0.05) between width of right lobe and width and length of left lobe of Common kestrel compared with White throated kingfisher and Laughing dove. While there was no significant difference (P>0.05) between the length and width of the right and left lobes in throated Kingfisher compared with Laughing dove. The color of liver was light brown-drak red in Laughing dove and light red in White-throated Kingfisher while dark brown-red in Common Kestrel. The percentage of the liver weight in laughing dove represents the higher rate when it compared with Common Kestrel and White-throated Kingfisher. In histological study, our results explained that the liver in the three species of birds were surrounded by a thin layer of dense connective tissue called Glissons capsule. It divided into unclear and irregular lobules and the central vein represent the core of each lobule. From the central vein, the hepatic laminae which consist of one to two layers of hepatic cells were branched, anatomizing, and radically extend to the periphery of the lobule blood sinusoids lining with endothelium and few number of large. The lobules surrounded by portal are a peripherally which made from dense connective tissues , it constitutes of portal vein, hepatic artery, and bile duct, in addition to lymphatic vessels which lining by endothelium.Keywords: Liver, Common Kestrel, White-throated Kingfisher and Laughing dove.